Effects of surgical correction of class III malocclusion on the pharyngeal airway and its influence on sleep apnoea. Issue 12 (December 2016) - Canellas, J.V. dos S.; Barros, H.L.M.; Medeiros, P.J.D.; Ritto, F.G.
Abstract: The objective of this study was to evaluate, through cone beam computed tomography, the immediate changes in pharyngeal airway space (PAS) after orthognathic surgery in class III patients, and to determine the influence of surgery on the development of obstructive sleep apnoea hypopnoea syndrome (OSAHS). A prospective study was conducted; 33 patients were divided into three groups: mandibular setback surgery (nine patients), bimaxillary surgery (18 patients), and maxillary advancement surgery (six patients). PAS measurements obtained pre- and postoperatively were compared using the t -test. All patients were assessed clinically for OSAHS before surgery and at 6 months postoperative using the Berlin questionnaire and a combined clinical assessment, which included the assessment of OSAHS symptoms, Epworth Sleepiness Scale score, and body mass index. Patients undergoing isolated mandibular setback surgery demonstrated a decrease in total PAS volume, in hypopharynx volume, and in minimum cross-sectional area of the pharynx immediately after surgery ( P  < 0.05). The clinical analysis did not reveal signs or symptoms of OSAHS in any of the 33 patients. Although patients who underwent mandibular setback surgery alone demonstrated a volume reduction in the PAS and a decrease in minimum cross-sectional area, these reductions were not accompanied by signs or symptoms of OSAHS.